Impact of the Waco Branch Davidian Case and the Anticult Movement in Post-Communist Hungary - Fazekas, Csaba (Nova religio, 2022)
This article examines the ways Hungarian political life and public debate were influenced by the news media's coverage of the 1993 conflict involving the Branch Davidians living at Mount Carmel Center near Waco, Texas and United States federal agents, in which a total of eighty-six people were killed. After the collapse of the Soviet political system, new religious movements began spreading rapidly in Eastern European nations at the beginning of the 1990s. The first anticult movements in Hungary were closely connected to the political conservativism and traditional religiosity represented by so-called "historical" Christian churches. The conservative governing parties aimed to restrict new religious movements by withdrawing financial support and by enacting a new law on religion and denominations resulting in anticult propaganda disseminated by the state. The news about the conflict and deaths at Mount Carmel Center played an important catalyzing role in the anticult parliamentary and press debates in Hungary. The tragedy of the deaths at Mount Carmel became one of the most important arguments in the hands of politicians in Hungary who wanted to limit freedom of religion for members of new religious movements.